Accuracy assessment of quasi-seamless hydrographic separation models in Malaysian waters - Hamden, Mohammad Hanif; Din, Ami Hassan Md; Alihan, Nur Surayatul Atikah; Pa’Suya, Muhammad Faiz; Wijaya, Dudy Darmawan; Che Cob, Ahmad Sanusi (Frontiers in Earth Science, 2023)
The hydrographic survey reduction using ellipsoid has been available since the advent of the global navigation satellite system (GNSS), with a potential to streamline operation and enhance bathymetric output. Spatially continuous separation surfaces connecting a chart datum (CD) to a geodetic ellipsoid is required for this technique. Universiti Teknologi Malaysia (UTM) has invented a new quasi-seamless separation model for Malaysian waters, known as the Malaysian Vertical Separation (MyVSEP) model, through semi-empirical models to capture the spatial variability of a tidal datum between coastal and offshore areas. A continuous vertical datum is established to develop MyVSEP models by combining the coastal and offshore datasets. The coastal datasets referred to the vertical reference point computed from coastal tide gauges, while the offshore datasets referred to the vertical reference surfaces derived from satellite altimetry. Mean sea level (MSL) or mean sea surface (MSS), mean dynamic topography (MDT), lowest astronomical tide (LAT), and highest astronomical tide (HAT) are the vertical datums involved in developing the continuous MyVSEP model. However, the integration of the vertical datum has only been conducted over the Peninsular Malaysia region. For Sabah and Sarawak, datum integration cannot be implemented due to the limitation of coastal datasets. The assessment of the integrated vertical datum with coastal tide gauges is discussed in this study. The finding shows that the root mean square error (RMSE) agreement between the integrated Universiti Teknologi Malaysia 2020 (iUTM20) model and coastal tide gauges yields below 2.0 cm. The iUTM20 lowest astronomical tide and highest astronomical tide models also show significant improvement compared to the altimetric-derived tidal models, which recorded the root mean square error agreement with coastal tide gauges of 1.8 cm and 2.0 cm, respectively. The development of a continuous vertical separation model for the Ellipsoidally Referenced Surveying technique indirectly optimizes marine geospatial information resources, especially for the National Hydrographic Centre in Malaysia.